Molecular analysis of the dominant homeotic Antennapedia phenotype - Schneuwly, Stephan (1987)
Most of the dominant alleles of the homeotic gene Antennapedia (Antp) which show a transformation of antennae into legs are associated with large chromosomal inversions. To determine the molecular mechanisms underlying the dominant phenotype, one of the strongest Antp alleles (Antp(73b)) was studied in more detail. The mutant chromosome has been cloned and the structure of the inversion has been identified. The inversion breaks two genes apart: the Antp gene and a previously unidentified gene, tentatively called responsible for dominant phenotype (rfd), located at 84D1-2. The two genes are transcribed in opposite directions and the breakpoints lie within introns of both genes. Through the inversion event, a reciprocal exchange of the first exons including promoters occurred leading to the production of new transcripts. The transcripts containing the entire Antp protein coding region which have been fused to the promoter of the rfd gene are lost in revertants of the dominant phenotype indicating a correlation between this fusion gene and the dominant phenotype. The molecular structure of inversion Antp(73b) suggests that the dominant phenotype arises via ectopic expression of the normal Antp protein due to a gene fusion event.